2022
DOI: 10.1097/gme.0000000000001941
|View full text |Cite
|
Sign up to set email alerts
|

The effect of music therapy on menopausal symptoms and depression: a randomized-controlled study

Abstract: Objective: Menopausal syndrome generally includes psychological problems. Listening to music has been used to cope with changes during this period. This study was conducted to determine the effect of listening to music on the symptoms of menopause and depression levels.Methods: This randomized-controlled study was carried out between July 2019 and December 2020. The study sample consisted of 48 postmenopausal women (21 in the music group and 27 in the control group). Music was played by the researcher to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…In addition, findings from our study are consistent with a meta-analysis by Aalbers et al, 28 reporting that music therapy reduces depression in the short term and depression and anxiety when combined with other treatments. It also agrees with the findimgs of Koçak and Varişoğlu 19 that music therapy can positively impact the quality of life by decreasing anxiety, depression, and stress indices. Finally, our statistical analysis is similar to a qualitative study of music therapy by Hohmann et al, 53 reporting improvements in emotional expression, interaction with others, development of skills in the use of music, and quality of life.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, findings from our study are consistent with a meta-analysis by Aalbers et al, 28 reporting that music therapy reduces depression in the short term and depression and anxiety when combined with other treatments. It also agrees with the findimgs of Koçak and Varişoğlu 19 that music therapy can positively impact the quality of life by decreasing anxiety, depression, and stress indices. Finally, our statistical analysis is similar to a qualitative study of music therapy by Hohmann et al, 53 reporting improvements in emotional expression, interaction with others, development of skills in the use of music, and quality of life.…”
Section: Discussionsupporting
confidence: 90%
“…In line with these results, the hypothesis “H5: Music affects menopausal symptoms in menopausal women” was supported. There are very few studies examining the effects of music on menopausal symptoms 5,28 . In their study examining the effects of music therapy on menopausal symptoms and depression, Varişoğlu 28 found that the posttest mean MRS total and subscale scores of the music group were 99% lower than their mean pretest scores.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few studies examining the effects of music on menopausal symptoms 5,28 . In their study examining the effects of music therapy on menopausal symptoms and depression, Varişoğlu 28 found that the posttest mean MRS total and subscale scores of the music group were 99% lower than their mean pretest scores. In a study by Bhave et al 5 on 60 menopausal women, it was determined that music therapy significantly reduced stress in the participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The core concept of MDT was patient-centered, individualized and continuously comprehensive treatment schemes for specific diseases based on the multidisciplinary team, which has been widely used over the world in recent years ( 42 ). Meanwhile, we innovatively combined music therapy in MHELM, which can relieve depression and menopausal symptoms to a large extent ( 43 ). Secondly, health education sessions were culturally accepted, multifaceted and well-designed program based on lifestyle medicine theoretical framework.…”
Section: Discussionmentioning
confidence: 99%